'It is designed for everybody to find their own level and to improve themselves'; views of older people and instructors of the Falls Management Exercise (FaME) programme. (12th February 2022) - Gumber, Leher; Timmons, Stephen; Coupland, Carol; Gladman, Johnrf; Iliffe, Steve; Kendrick, Denise; Lafond, Natasher; Logan, Pip; Masud, Tahir; Skelton, Dawna; Orton, Elizabeth
Abstract: Background: Older adults are at increased risk of falls due to ageing, decreased muscle strength and impaired balance. Clinical trials have demonstrated the efficacy and effectiveness of the Falls Management Exercise (FaME) programme in improving functioning and preventing falls. However, programme completion is often low, impacting the potential benefits of FaME. Objective: To explore the barriers and facilitators for participation and completion of the FaME programme from an instructor and participant perspective. Methods: Semi-structured interviews were conducted with 20 FaME users and seven Postural Stability Instructors from the East Midlands region of England, UK. Interviews were conducted using a topic guide and explored their views of the programme, intended benefits, reasons for participating, instructor's approach and venue facilities. Data were transcribed verbatim and analysed using thematic analysis. Written informed consent was obtained from all participants and instructors. Results: Common themes identified by participants and instructors for adherence related to perceived health benefits, psychological well-being, intervention characteristics, cost, instructors' qualities, opportunity to socialise, venue accessibility and facilities. Further factors such as maintaining independence, discipline, relationship with peers and caring responsibilities influenced participants' engagement with the programme. Instructor factors such as progression were also reported as important predictors. Conclusions: Instructor and participant factors influence uptake, attendance and adherence of FaME. The findings from this study can inform the development and improvement of additional falls-prevention programmes. It can also guide marketing strategies to promote uptake of exercise-based falls-prevention programmes among older adults.